Prosody in Young Verbal Children With Autism Spectrum Disorder. - McAlpine, Ashlynn; Plexico, Laura W.; Plumb, Allison M.; Cleary, Julie (Contemporary Issues in Communication Science & Disorders)
Purpose: The purpose of this study was to examine the expressive prosody of young verbal children with autism spectrum disorder (ASD). Method: Vocalizations were examined in 14 children between 24 and 68 months of age: 7 diagnosed with ASD and 7 with typical development, matched for expressive language abilities. To obtain precise measures of prosody, spontaneous speech samples were obtained and then coded using The Prosody Voice-Screening Profile (PVSP; Shriberg, Kwiatkowski, & Rasmussen, 1990). Results: The 2 groups did not differ in their production of rate, loudness, or pitch. The group with ASD did, however, produce atypical stress patterns significantly more often, such as misplacement of stress in multisyllabic words or reduced stress. Conclusion: Results of the current investigation highlight the importance of considering prosody, specifically misplaced stress, when assessing and treating young children with ASD.